Residential racial segregation and social distancing in the United States during COVID-19 - White, Alexandre (EClinicalMedicine, 2021)
BACKGROUND: Our objective is to examine whether residential racial segregation may be constraining capacities for social distancing thus leaving African Americans potentially more exposed to contracting COVID-19. We hypothesized that residential racial segregation constrains African Americans’ spatial mobility when the whole population is locked down but increases their need for moving under reopening orders. METHODS: We employ a Black/White dissimilarity index as our independent variable and county-level mobility ratios as our dependent variable. Using generalized estimating equations for longitudinal data, we analyzed the effects of Black/White segregation on population mobility by counties across the United States from March 8 to August 7, 2020 under two different COVID-19 related policy conditions: lockdown and reopening. FINDINGS: While higher county-wide levels of segregation were significantly associated with decreased mobility under lockdown and stay-at-home orders, we found that this relationship between segregation and mobility dissipated under reopening orders. INTERPRETATIONS: Investigating the effects of health policy without considering differing effects due to structural racism will likely ignore complexities that may create unintended consequences of health policy. Our conclusions suggest African Americans may face structural limitations to effective social distancing as evidenced by higher rates of mobility after reopening policies go into effect.